Performance of multigap RPC detectors in the HARP experiment - Barr, G; Dedovich, D; De Min, A; De Santo, A; Dydak, F; Koreshev, V; Linssen, L; Pattison, C; Robbins, S; Wotschack, J (2004)
A time-of-flight system based on 46 multigap glass resistive plate chambers has operated for 2 years in the HARP experiment at the CERN PS. The system covers an area of 10m(2) and comprises 368 readout channels. Systematic checks of the RPC performance are presented as well as preliminary results on its particle identification capabilities. (C) 2004 Elsevier B.V. All rights reserved.